2016
DOI: 10.1080/21623945.2016.1191307
|View full text |Cite
|
Sign up to set email alerts
|

Exercise regulation of adipose tissue

Abstract: Exercise training results in adaptations to numerous organ systems and offers protection against metabolic disorders including obesity and type 2 diabetes, and recent reports suggest that adipose tissue may play a role in these beneficial effects of exercise on overall health. Multiple studies have investigated the effects of exercise training on both white adipose tissue (WAT) and brown adipose tissue (BAT), as well as the induction of beige adipocytes. Studies from both rodents and humans show that there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 76 publications
(137 reference statements)
2
91
1
3
Order By: Relevance
“…Given that exercise also increases energy expenditure and heat production, it would not be surprising if BAT was downregulated with exercise to maintain body temperature. However, studies investigating the effects of exercise on BAT have yielded conflicting results (Stanford and Goodyear, 2016). In some studies, investigators have shown an increase in mitochondrial activity in rodent BAT (Ignacio et al, 2012;Yoshioka et al, 1989), whereas other studies have revealed a decrease in mitochondrial activity (Wu et al, 2014) and glucose uptake in BAT in exercise-trained humans (Vosselman et al, 2015;Motiani et al, 2017).…”
Section: The Curious Effects Of Exercise On Batmentioning
confidence: 98%
See 3 more Smart Citations
“…Given that exercise also increases energy expenditure and heat production, it would not be surprising if BAT was downregulated with exercise to maintain body temperature. However, studies investigating the effects of exercise on BAT have yielded conflicting results (Stanford and Goodyear, 2016). In some studies, investigators have shown an increase in mitochondrial activity in rodent BAT (Ignacio et al, 2012;Yoshioka et al, 1989), whereas other studies have revealed a decrease in mitochondrial activity (Wu et al, 2014) and glucose uptake in BAT in exercise-trained humans (Vosselman et al, 2015;Motiani et al, 2017).…”
Section: The Curious Effects Of Exercise On Batmentioning
confidence: 98%
“…However, this mechanism does not make sense in the context of exercise-induced beiging because exercise increases heat production (Saugen and Vøllestad, 1995). Several hypotheses have been proposed as the underlying mechanism (Stanford and Goodyear, 2016), one of which is increased sympathetic innervation, which is known to occur in scWAT during exercise (Nedergaard et al, 2014;Ranallo and Rhodes, 1998). Other hypotheses focus on the exercisestimulated release of myokines, including irisin (Boström et al, 2012), myostatin (Feldman et al, 2006), meteorin-like 1 (Metrnl) (Rao et al, 2014), lactate (Carriere et al, 2014) and β-aminoisobutyric acid (BAIBA) (Roberts et al, 2014), as well as other secreted factors, including brain-derived neurotrophic factor (BDNF) (Cao et al, 2011).…”
Section: Exercise Causes Beiging In Rodent Scwatmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some cytokines (e.g., IL-6 and TNF-a, among others) derived from adipose tissue or skeletal muscle, various nutrients and metabolites can induce browning (5,6). Although it seems reasonable to increase thermogenesis during cold exposure, it may seem counterintuitive to increase thermogenesis under conditions such as exercise and metabolic stress.…”
mentioning
confidence: 97%